1975
DOI: 10.1017/s0033291700056452
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of classes of personal illness

Abstract: SynopsisA hierarchy of classes of personal illness model is proposed and was assessed using a new self-report measure, the Delusions-Symptoms-States Inventory (DSSI). Of 480 psychiatric patients 93.3% had symptom patterns conforming to the model. It was additionally found that single syndrome patterns, within a particular class, occurred significantly more often in those not classifiable in any higher class. Finally, the relationship between each possible pair of the 12 syndromes was examined. Some of the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
0
2

Year Published

1976
1976
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(105 citation statements)
references
References 7 publications
6
97
0
2
Order By: Relevance
“…Additional validity is suggested by a study of 200 normal persons compared to 480 patients (Bedford and Foulds 1978). The hierarchical model of mental illness advanced by Foulds and Bedford (1975) has been repeatedly confirmed (Bagshaw 1977;Gilleard 1983;Morey 1985;Palmer et al 1981). Despite Cox et al's (1983) suggestion to the contrary, we have found the DSSI-D sensitive to change using a sample of recently bereaved mothers and fathers (Boyle et al 1996).…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Additional validity is suggested by a study of 200 normal persons compared to 480 patients (Bedford and Foulds 1978). The hierarchical model of mental illness advanced by Foulds and Bedford (1975) has been repeatedly confirmed (Bagshaw 1977;Gilleard 1983;Morey 1985;Palmer et al 1981). Despite Cox et al's (1983) suggestion to the contrary, we have found the DSSI-D sensitive to change using a sample of recently bereaved mothers and fathers (Boyle et al 1996).…”
Section: Methodsmentioning
confidence: 88%
“…The inventory was developed according to the theory that mental health problems can be ranked along a continuum according to the extent to which the individual increasingly loses control of his/her own behaviour and personal relationships (Foulds and Bedford 1975;Heather 1977). All seven symptoms of the DSSI appear to address both the ICD-10 and DSM-IV indicators of depression.…”
Section: Methodsmentioning
confidence: 99%
“…It contains 14 symptoms, 7 for depression and 7 for anxiety. The DSSI was developed for use with community samples and has been validated against clinical samples with diagnosed mental illness [29][30][31], and was also found to correlate well, and shares items with, other established symptoms scales such as the Edinburgh Postnatal Depression Scale (EPDS) and the Hospital Anxiety/Depression Scale (HADS) [32]. Participants in this study were classified as anxious when they reported four or more symptoms.…”
Section: Measurement Of Depression and Anxiety Symptomsmentioning
confidence: 99%
“…This personality instrument is reasonably reliable and valid (Eysenck, 1991). The DelusionsSymptoms-States Inventory or DSSI (Foulds & Bedford, 1975) measures the mood states of anxiety and depression used as stress measures in the present study.…”
Section: Instrumentsmentioning
confidence: 99%